Menguatkan Nilai Integritas Melalui Sosialisasi Anti-Korupsi di Lingkungan Pendidikan - Zahra Amanda (Politeknik Negeri Padang, 2025)
Corruption is one of the biggest challenges facing Indonesia,destroying publick trust and hindering national development. This aims to analyse the implementation of anti-corruption literacy outreach in school, including methods, challenges and impacts on students. This research uses a qualitative descriptive approach, whit data collected through interviews, observation and documentation in several primary and seconday schools. The results of the research show that thesocialization of anti-corruption literacy has been carried out throught the integration of anti-corruption values in the curriculum and campaigns. Despite facing obstacles such as limitide resources and lack of teacher training, thi program has had a positive impact on students’ understanding of the dangers of corruption, strengthening the values of honesty and integrirty.